Analisis Pengelolaan di Instalasi Gizi Rumah Sakit Islam Nashrul Ummah Lamongan - Faizatul Ummah; Mista Ainin Oktafia (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
The nutrition installation is one of the important service facilities in the hospital, which starts from planning, providing, organizing to distributing food to patients. This study uses a qualitative method with direct observation and interviews at the Nashrul Ummah Lamongan Islamic Hospital nutrition installation consisting of waste identification, risk assessment, and identification of the causes of problems using fishbone. Based on the results of the analysis using the waste identification method, it is known that food ingredient management officers still often do not use PPE in accordance with existing standards, this is included in the waste defect category. To determine the risk category, a risk assessment is carried out which is known to have a medium category and must get special attention from the hospital. Then the fishbone identification is carried out and the root of the problem is found in the man part consisting of awareness to do personal hygiene is still not optimal, officer knowledge about personal hygiene still needs to be improved, lack of officer awareness of the use of PPE and lack of officer compliance with the process flow of procurement, management and distribution, method, namely lack of understanding of officers related to SPO in the nutrition installation, and material consists of the availability of existing PPE, but not optimal in its use, not doing food laboratory checks, not doing medical checkups regularly, the need for posters about the virtues of personal hygiene. To overcome this, you can use the PDSA analysis method. The conclusion of this study is that Nashrul Ummah Lamongan Islamic Hospital must carry out procedures related to the use of PPE that are complete according to the SPO used, conduct strict supervision from PPI, and make posters on the use of PPE in the nutrition installation.